2019
DOI: 10.1117/1.jbo.24.12.121910
|View full text |Cite
|
Sign up to set email alerts
|

Multidomain computational modeling of photoacoustic imaging: verification, validation, and image quality prediction

Abstract: As photoacoustic imaging (PAI) technology matures, computational modeling will increasingly represent a critical tool for facilitating clinical translation through predictive simulation of real-world performance under a wide range of device and biological conditions. While modeling currently offers a rapid, inexpensive tool for device development and prediction of fundamental image quality metrics (e.g., spatial resolution and contrast ratio), rigorous verification and validation will be required of models use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 58 publications
(95 reference statements)
0
25
0
Order By: Relevance
“…The credibility of such simulation models needs to be assessed through parametric verification and validation studies against the experiments. Towards this goal, several PAI simulation approaches have been proposed to optimize the PAI device geometries and quantitative image reconstruction [ [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. These simulations have been predominantly reported for photoacoustic computed tomography geometries that involve rotating single element transducers or sparsely distributed ultrasound transducer elements [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The credibility of such simulation models needs to be assessed through parametric verification and validation studies against the experiments. Towards this goal, several PAI simulation approaches have been proposed to optimize the PAI device geometries and quantitative image reconstruction [ [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. These simulations have been predominantly reported for photoacoustic computed tomography geometries that involve rotating single element transducers or sparsely distributed ultrasound transducer elements [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite rapid progress in the development and clinical translation of dual-modality USPA devices, no simulation studies have been reported to the best of our knowledge for modeling dual-modality B-mode US and PA imaging of realistic heterogeneous tissue medium. Recently, PAI simulations using k-Wave toolbox have become popular [ 38 , [37] , [38] , [39] , [40] , [41] , [42] ]. Since k-Wave models only acoustic wave propagation, majority of these PAI simulations assumed uniform optical fluence across tissue depth [ 33 , 42 ], while some studies employed light transportation models such as NIR Fast [ 38 ] or Monte Carlo [ 39 ] for estimating light fluence inside homogenous tissue medium and subsequently converting the fluence into initial pressure distribution, followed by photoacoustic reconstruction using k-Wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The credibility of such simulation models needs to be assessed through the extensive verification and validation studies against the experiments. Towards this P goal, several PAI simulation approaches have been proposed to optimize the PAI device geometries and quantitative image reconstruction [28][29][30]. These simulations have been predominantly reported for photoacoustic computed tomography geometries that involve rotating single element transducers or sparsely distributed ultrasound transducer elements [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, K-Wave does not account for the realistic PAI scenarios where the optical fluence strongly depends on the heterogeneous optical properties of the tissue, irradiation wavelength and attenuates as a function of tissue depth. Nima et al [29] recently used Monte Carlo simulations for estimating optical fluence in a homogeneous tissue phantom and reconstructed PA images using K-Wave toolbox. However, this study did not report B-mode US images to display corresponding structural information of the tissue phantom.…”
Section: Introductionmentioning
confidence: 99%